(untitled) (Revista Brasileira Multidisciplinar, 2025)
This study investigated the potential of starch extracted from babassu mesocarp for use in the food industry. Starch from babassu mesocarp was extracted alkaline and its physical-chemical and functional characteristics such as syneresis, transparency and amylose content were evaluated, comparing the data with conventional corn and cassava starch. The results showed that babassu starch has a satisfactory degree of purity when the proximate composition was analyzed, which included moisture (12.65%), proteins content (0.27%), lipids (0.01%), ashes (0.00%). A high amylose content (29.19%) was found, which could be a viable alternative for applications as a thickening and binding agent. Although transparency has decreased over time (7.03% to 3.27%), this characteristic can be useful in certain products. Differences were observed in relation to cassava and corn starches in terms of syneresis, where babassu starch presented the highest value (35.70%), water absorption was also higher for babassu starch (2.19%) and solubility in water it was the lowest (0.13%). Therefore, adaptation of formulations is necessary to optimize their performance in various industrial applications. This study contributes to diversification and innovation in the food industry, paving the way for the wider use of babassu starch.